PERSONALITY TRAITS AND LANGUAGE LEARNING: A SCIENTIFIC APPROACH TO INTELLECTUAL STRUCTURE AND INFLUENTIAL CONSTITUENTS - M. H., Raamkhumar; Kumar, Shanmugam Senthil; VJP, Dinesh (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Language learning is a complex cognitive process that is influenced by various factors, including individual differences in personality traits. This study examines the intricate relationship between personality traits and language learning capacity. Through an extensive bibliometric analysis of existing literature, this study aims to shed light on how personality traits affect an individual’s ability to acquire and master new languages. By employing various bibliometric approaches, such as performance analysis, science mapping, and citation analysis, we seek to unveil the intellectual structure behind the correspondence of personality traits and language learning as findings that can open avenues and potential areas for future research. We also attempted to identify patterns that could help educators, language instructors, and learners. Ultimately, this study strives to bridge the gap between psychology and linguistics.